Cranial Cruciate Ligament Rupture in Dogs - Evaluation of Postoperative Results of the CBLO Technique - Mustafa Arıcan,; Birol Özdil,; Elgin Orçum Uzunlu,; Nuriza Zamirbekova,; Gümüş, Fehmiye (Acta Scientiae Veterinariae, 2024)
Background: A major cause of osteoarthritis (OA) in dogs is cranial cruciate ligament (CCL) rupture. Currently, many intra- and extra-articular treatment techniques are used for dogs with CCL tears. However, biomechanically based methods (Tibial Plato Levelling Osteotomy-TPLO, Tuberositas Tibia Advancemet -Standard TTA, TTA-Rapid) are often preferred. It has been suggested that it may be an alternative technique to prevent complications of the most commonly used TPLO, TTA and TTA-Rapid. The aim of this study was to evaluate the post-operative results of the Cora Base Levelling Osteotomy (CBLO) technique in dogs with cranial cruciate ligament (CCL) rupture. Materials, Methods & Results: Ten dogs of different breeds, ages and weights were used as material. The operation was started from the medial surface of the tibia. The injector needles were used to locate the joint for placement of the biradial saw. The medial collateral ligament was visualised. The popliteal muscle was reflected and the popliteal artery was protected. The osteotomy was stopped when 1/3-1/2 complete and the appropriate millimetre measurements were marked for osteotomy rotation. In the pre-operative planning, D1, the distance from the patellar tendon to the tibia, D2 and the caudal extension of the area where the saw was placed. The osteotomy was started. The osteotomy was completed, the desired rotation achieved and maintained with a stabilising pin. The plate was fixed. The bone plates used were a standard 3.5 mm CBLO (Intrauma, Fixin, Italy) and in some cases a wide TPLO plate. Progress in walking and running tests was noted in 7 cases (70%) compared to the preoperative period. Mild lameness after exercise was observed in 3 cases (30%). Surgery took an average of 30-40 min. It was also observed that the tibial plateau angle (TPA) decreased individually in the post-operative period. According to the results of the force plate gait analysis, there was an improvement in 5 cases (50%). No post-operative change was observed in 5 cases (50%). Radiographs of the A.genu in the medio-lateral and cranio-caudal positions were taken in the cases. The criteria used in the evaluation; the radiographs were interpreted taking into account criteria such as narrowing of the joint space, displacement of the "fat pad" in the joint, cranial rotation of the tibia, especially as a result of cranial cruciate ligament rupture, and osteophytic growth in the subchondral areas of the joint. Post-operative radiographs at day 1 and day 45 were compared. It was observed that the placement of the plate was good in all cases. Discussion: Therefore, the CBLO technique is an alternative technique to the TPLO and TTA techniques for CCL ruptures. The CBLO technique is an adjunct to the TPLO technique by preserving the proximal tibial epiphysis. Even in small breeds, a large amount of bone is available for stabilization in the proximal area. The compression screw and implant provide excellent bone contact. This ensures proper fixation and early function in recovery. Correction of the axis in the centre of the CORA has been observed to improve after proximal and distal rotation. There was no balcony effect as seen with TPLO. The joint was not damaged by the CBLO technique. However, there are some difficulties with the CBLO technique; learning the technique and handpieces. In particular, good preparation for the preoperative period for TPA and plate selection. A larger group of dogs is also needed for further studies and additional complications could be expected in the long-term evaluation. Keywords: CBLO, Force Plate Gait Analysis, Tibial Plateau Angle.